2017
DOI: 10.1016/j.aogh.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol to Develop Practice Guidelines for Primary Care Medical Service Trips

Abstract: B A C K G R O U N D North American clinicians are increasingly participating in medical service trips (MSTs) that provide primary healthcare in Latin America and the Caribbean. Literature reviews have shown that the existence and use of evidence-based guidelines by these groups are limited, which presents potential for harm.O B J E C T I V E This paper proposes a 5-step methodology to develop protocols for diagnosis and treatment of conditions encountered by MST clinicians. M E T H O D SWe reviewed the 2010 Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Likewise, the prevalence of pyoderma (i.e., impetigo, cellulitis, abscesses) is approximately 5–10% in tropical regions, according to the World Health Organization (WHO) . Finally, the reported prevalence of scabies on MSTs in Latin America and the Caribbean (LAC) appears to total between 3.3 and 4.3% of all patient complaints …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, the prevalence of pyoderma (i.e., impetigo, cellulitis, abscesses) is approximately 5–10% in tropical regions, according to the World Health Organization (WHO) . Finally, the reported prevalence of scabies on MSTs in Latin America and the Caribbean (LAC) appears to total between 3.3 and 4.3% of all patient complaints …”
Section: Introductionmentioning
confidence: 99%
“…Under such circumstances, best practice guidelines are critical to ensuring consistent clinical management in the field . Despite this, a recent integrative review demonstrated a lack of evidence of guideline use in MST practice in LAC . Many MST‐sending organizations, however, do distribute unpublished training protocols (also referred to as “gray literature protocols”) to support clinicians who travel with them.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations